Immune Inspired Framework for Ad Hoc Network Security - Yasir Abdelgadir , Mohamed; Azween, Abdullah (2009)
As a comprehensive security system, researchers recently have turned to the human immune system as a very wealthy source of inspiration. DNA computation, evolutionary computation, artificial neural networks, and artificial immune systems are some of the research interest which can be pointed out. By means of diverse kinds of cells, molecules, and mechanisms, the immune system efficiently protects the human body against different kinds of attacks. Many immune-inspired techniques have been developed with the aim to tackle different computing problems. Network security represents one of the most significant fields that the immune-inspired techniques have been applied to. Given that mobile ad hoc networks have a decentralized nature similar to the human immune system (HIS), immune-inspired security architecture is highly expected to come across different ad hoc security problems, one of which is the malicious node that can disrupt the routing process, masquerade as the legitimate nodes, and impersonate the trusted nodes. In this paper, immune-inspired security architecture for simulating a number of HIS processes for securing mobile ad hoc networks is presented. Both the negative selection and danger theory techniques have been combined along with many other inspired processes to come up with a scalable and robust system. Distributability, second response and self recovery of nodes, are the hallmarks of the proposed architecture.